Upaya Meningkatkan Kemampuan Membaca pada Aspek Mengeja Kata Melalui Gerakan Literasi Sekolah pada Siswa Kelas 1 di SDK JOGE - Tai, Maria Natalia Defatima; Ita, Efrida; Fono, Maria Yasinta; Dhiu, Konstantinus Dua (Global Action and Education for Society, 2024)
This research aims to improve the reading skills in the spelling aspect of grade 1 students at SDK Joge. This type of research uses a qualitative descriptive type with data collection methods in the form of observation, documentation interviews. The subjects in this research were 18 grade 1 students at SDK Joge. The results of this research show that literacy activities by implementing several programs, namely 1) reading habit 15 minutes before learning begins, 2) reading corner, 3) reading garden, 4) wall magazine, 5) provision of multilingual posters which are carried out at SDK Joge, especially in class 1 experiencing changes where children are able to read well and correctly. This can be seen from the results of observations before implementing the school literacy movement, there were 13 students who still had difficulty reading. After the School Literacy Movement (GLS) program was held, reading ability in the aspect of spelling words increased, where there were 15 students who were able to read well. From these activities, it can be concluded that the existence of the School Literacy Movement (GLS) program can improve the reading ability in the spelling aspect of grade 1 students at SDK Joge.